2017
DOI: 10.21608/ejchem.2017.745.1021
|View full text |Cite
|
Sign up to set email alerts
|

Amino acids combined chitosan nanoparticles for controlled release of Doxorubicin hydrochloride

Abstract: Complementing to our previous studies in biopolymers and amino acids for medical applications this study was addressed to design a unique therapeutic regime consisting of a cocktail from therapy with amino acids (TAAI) and polymer therapy for cancer disease. This regime is depending on synthesized Doxorubicin loaded chitosan-glutamic acid (Cs-Ga-DOX) nanoparticles via ionic gelation pathway. The encapsulation efficiency was 69%. The average size was 20-37 nm with spherical, homogenous structure, and positive z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…polyethylene glycol, polyacrylic acid, poly (vinyl pyrrolidone), poly (vinyl alcohol), poly (methacrylic acid) or natural, as in the case of chitosan, starch, cellulose, agarose, and dextran. Natural polymers, especially polysaccharide, are widely used in the field of drug delivery and biomedical applications [ 23 ]. Chitosan, the second most abundant biopolymer after cellulose, is an inexpensive, inert, hydrophilic, biocompatible support, and is thus attractive for drug delivery systems [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…polyethylene glycol, polyacrylic acid, poly (vinyl pyrrolidone), poly (vinyl alcohol), poly (methacrylic acid) or natural, as in the case of chitosan, starch, cellulose, agarose, and dextran. Natural polymers, especially polysaccharide, are widely used in the field of drug delivery and biomedical applications [ 23 ]. Chitosan, the second most abundant biopolymer after cellulose, is an inexpensive, inert, hydrophilic, biocompatible support, and is thus attractive for drug delivery systems [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, M. A. Abd El-Ghaffar loaded DOX in CsNPs and Cs-glutamate to improve EE. Their results demonstrated that as the DOX concentration was raised, the EE increased to reach the highest concentration of 69% for copolymer/DOX and 30% for CsNPs/DOX [32].…”
Section: Determination Of Drug Ee and DLmentioning
confidence: 99%
“…the variation of the values of the nano sized depending on to the type and the nature of material applied. [20,21] Zeta Potential Study Zeta potential is a significant parameter representing the stability of drug particles measured, i.e. not change in chemical structure or physical modification of drugs (5-FU), (DOX) and (CA).…”
Section: Transmission Electron Microscopy (Tem)mentioning
confidence: 99%